Large-scale glacitectonic deformation in response to active ice sheet retreat across Dogger Bank (southern central North Sea) during the Last Glacial Maximum. (1st January 2018) - Phillips, Emrys; Cotterill, Carol; Johnson, Kirstin; Crombie, Kirstin; James, Leo; Carr, Simon; Ruiter, Astrid
Abstract: High resolution seismic data from the Dogger Bank in the central southern North Sea has revealed that the Dogger Bank Formation records a complex history of sedimentation and penecontemporaneous, large-scale, ice-marginal to proglacial glacitectonic deformation. These processes led to the development of a large thrust-block moraine complex which is buried beneath a thin sequence of Holocene sediments. This buried glacitectonic landsystem comprises a series of elongate, arcuate moraine ridges (200 m up to > 15 km across; over 40–50 km long) separated by low-lying ice marginal to proglacial sedimentary basins and/or meltwater channels, preserving the shape of the margin of this former ice sheet. The moraines are composed of highly deformed (folded and thrust) Dogger Bank Formation with the lower boundary of the deformed sequence (up to 40–50 m thick) being marked by a laterally extensive décollement. The ice-distal parts of the thrust moraine complex are interpreted as a "forward" propagating imbricate thrust stack developed in response to S/SE-directed ice-push. The more complex folding and thrusting within the more ice-proximal parts of the thrust-block moraines record the accretion of thrust slices of highly deformed sediment as the ice repeatedly reoccupied this ice marginal position. Consequently, the internal structure of the Dogger Bank thrust-moraine complexes can be directly related to ice sheet dynamics, recording the former positions of a highly dynamic, oscillating Weichselian ice sheet margin as it retreated northwards at the end of the Last Glacial Maximum. Highlights: Structural architecture of a glacitectonic landsystem, Dogger Bank, North Sea. Detailed study using high-resolution 2D seismic data. Large-scale glacitectonics at an oscillating margin during surge-related readvance. Deformation during Weichselian ice sheet retreat in the southern central North Sea.